Andragogy Approach to Arabic Language Learning for Hajj Pilgrims at Kbihu Al-Ittihaad, Magelang Regency in 2023 - Iqdam Aun Rafiq (Universitas Syiah Kuala, 2023)
This study aims to evaluate the effectiveness of the approach, as well as to understand its impact on the understanding of Arabic language and the appreciation of Arabic cultural values in pilgrims. The research method used in this article is qualitative descriptive method. This method was chosen to describe in detail and in depth the application of the andragogy approach to Arabic language learning for Hajj pilgrims at KBIHU Al-Ittihaad, Magelang Regency in 2023. The results of this study conclude that the andragogy approach has proven to be the right learning model in the context of learning Arabic for Hajj pilgrims at KBIHU Al-Ittihaad, Magelang Regency in 2023. By continuing to optimize its application and providing appropriate support for teachers, it is hoped that learning Arabic for pilgrims will further improve the quality of their experience in performing Hajj and develop a deep understanding of Arabic language and Arabic cultural values.